Pengaruh Kepercayaan Dan Keamanan Terhadap Keputusan Berdonasi Melalui Financial Technology Crowdfunding Platform Di Jabodetabek - Nabila Dewi Oktaviona; Mariah Mariah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the effect of Trust and Security on the decision to donate through a financial technology crowdfunding platform. This type of research is quantitative research. The data collection method used in this study was to distribute questionnaires. For sampling using the technique of Probability Sampling with Simple Random Sampling technique. The sample is 96 people. The criteria for this research respondent are domiciled in JABODETABEK and have made a decision to donate through a crowdfunding platform in Indonesia at least once. The results of this study state that the percentage influence of trust (X1) and security (X2) simultaneously has a significant effect on the decision to donate (Y).